On The Performance of Mach-Zehnder-Interferometer (MZI) Optical Modulator on Silicon-On-Insulator (SOI) - Razak, HA; Haroon, H; Suhaila, A; Zain, M; Menon, PS; Shaari, S; Mukhtar, WM (IEEE, 2024)
In recent years, there has been a significant interest in the development of optical waveguide modulators using Silicon-On-Insulator (SOI) substrates motivated by the potential to provide a reliable low-cost alternative to other photonic materials. Objective: In this paper, Multimode Interference (MMI) device is used to develop the MZI structure of the optical modulator. Meanwhile, the electrical part of the modulator utilizes the forward biased P-I-N structure. The effect of varying MMI width to the performance of the MZI optical modulator on SOI was investigated. The effect of varying MMI width to the insertion loss (IL), extinction ratio (ER) and modulation efficiency (V pi L) of the device were carried out. Results: The investigated MMI widths are 22, 30 and 38 mu m. Smallest MMI width, which is 22 mu m has recorded the lowest value of insertion loss with 3.30 dB and the best extinction ratio of 25.60 dB. However, the best modulation efficiency was observed for the MMI width of 38 mu m with 0.1696 V.cm. Conclusion: Appropriate selection of MMI width is vital to ensure optimum performance of the MZI modulator.